Biologicals and biosimilars: gaps in the pharmacovigilance system in Portugal - Portela, Edit Maria da Conceição Constantino (2017)
Introduction: Biological and biosimilar medicinal products have specific characteristics that call for a closer monitoring of their safety profile. Since the current legal framework stems from both European and national regulations, some gaps in the operational field may be expected. The goal of this paper is to identify these gaps and propose changes to the current information systems and pharmacovigilance regulations. Material and Methods: A qualitative analysis of current pharmacovigilance regulatory framework and supporting information system was conducted. Results: Current pharmacovigilance system does not seem to vouch for the safe use of biologicals and biosimilar drugs. The gaps found in reviewed materials may be attributable to their lack of specificity for biopharmaceuticals. Discussion: Biologicals therapy presents specific determinants related with the drugs, prescription, and traceability, without replication in any other segment of the pharmaceutical market. They are able to shape their safety profile. Conclusion: The existing pharmacovigilance’s regulatory framework should be adjusted in order to improve the safety related with biopharmaceutical therapy. Some intervention measures are proposed.